Skin Permeation of Candesartan Cilexetil from Transdermal Patch Containing Aloe Vera Gel as Penetration Enhancer - Sharma, Kiran (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To prepare and evaluate the matrix type transdermal films of candesartan cilexetil (CC) containing Aloe vera gel as penetration enhancer by solvent evaporation technique to enhance its bioavailability. Material and Methods: Eudragit-RL 100 and hydroxypropyl methylcellulose (HPMC) were used as film former and dibutyl phthalate (DBP) as a plasticizer. A. vera gel was employed as a penetration enhancer to improve the skin penetration of CC by a probable pull effect of complexes formed between the drug and the enhancing agent (lignin). The film preparations were characterized in physicochemical properties such as thickness, folding endurance, uniformity of drug content, stability, and tensile strength. In vitro drug release and skin permeation kinetics studies of CC from film preparations were examined using a Franz-type diffusion cell. Infra-red spectroscopy and differential scanning colorimetry were performed to follow drug-carrier interactions. Results and Discussion: The uniformity of drug content was evidenced by the low standard deviation values for each film preparation. Enhancers examined in this study increased the moisture uptake capacity and release rate of CC, as by increasing the concentration of a. vera gel from 5% to 10% w/w in the film enhanced the release rate of CC substantially. Skin irritation studies revealed that there was no erythema and edema at the site of application. Conclusion: The study indicates that the candesartan could be administered transdermally for the effective control of hypertension through the matrix type TDDS having suitable mechanical properties and high bioavailability. Based on the observation, we can reveal that a11 formulation is better suited for development with compositions ERL 100: HPMC (5:5), DBP 5 ml with a. vera gel 10% (w/w) provided with a high skin permeation rates.